PENGARUH KONSENTRASI PUPUK NPK CAIR DAN JUMLAH RUAS STEK PUCUK TERHADAP PERTUMBUHAN TANAMAN NILAM (Pogostemon cablin Benth) - Rina Afrianti Tudu; Hertasning Yatim; Mihwan Sataral (Jurnal Ilmiah Mahasiswa Fakultas Pertanian, 2021)
The good quality patchouli plants, it takes patchouli cuttings that have good initial vegetative growth. The initial vegetative growth in plants is an important phase that supports the further growth of patchouli until the productive phase. To produce patchouli plants with good initial vegetative growth, fertilization is necessary to ensure the availability of nutrients needed in the metabolic process of patchouli plants. Patchouli plants require adequate amounts of nutrients, especially macro nutrients such as nitrogen and others which can be done by administering NPK with the right dose and frequency of administration. The results showed that (1) the treatment of patchouli cuttings (treatment B) had a very significant effect on the growth of patchouli at week 2,4,6,8,10 and 12 WAP. Meanwhile, the concentration of liquid NPK fertilizer (treatment A) had a very significant effect only at the age of 10 and 12 WAP for the number of leaves. (2) The treatment of the number of patchouli cuttings (treatment B) had a significant effect on the growth of patchouli at week 4 WAP, had a very significant effect at week 2,6,8 and 12 WAP. As for the treatment, the concentration of liquid NPK fertilizer (treatment A) had a significant effect on week 8 MST and had a very significant effect at week 10 and 12 MST for the number of shoots (3) There was an interaction between the two treatments, namely at the age of 10 and 12 MST while on the number of shoots only occurred at the age of 12 MST